Interaction between trait and housing condition produces differential decision-making toward risk choice in a rat gambling task - Wha Young Kim (Nature Portfolio, 2017)
Abstract Poor decision-making is a core problem in psychiatric disorders such as pathological gambling and substance abuse. Both trait and environmental factors are considerably important to affect decision-making. However, it has not yet been systematically shown how they interact to affect risk preference in animal models evaluating decision-making. Here, we trained rats, housed in pairs or in isolation, in a touch screen chamber to detect the association between four different light signals on the screen and accompanied reward and punishment outcomes arranged with different schedules. Then, the rats were allowed to freely choose from 4 different light signals. Once animals showed a stabilized pattern of preference (risk-averse or risk-seeking), they were injected with saline or cocaine (a single injection per day for 7 days) followed by 2 weeks of withdrawal. Then, their preference of choice was re-tested in the touch screen chamber while they were cocaine challenged. All rats significantly changed their preference toward more risky choices when they were exposed to and challenged with cocaine, except those in the risk-averse/isolated housing group. These results indicate that the pre-existing trait toward risk and the housing condition interact to affect the quality of decision-making, and cocaine may help to aggravate this process.